Utilization of organic fertilizer to increase paddy growth and productivity using System of Rice Intensification (SRI) method in saline soil - V O Subardja; I Anas; R Widyastuti (Brawijaya University, 2016)
Soil salinity has negative effect on soil biodiversity as well as microbial activities. Hence, rice growth also effected by salinity. Application of organic fertilizer and adoption of System of Rice Intensification (SRI) cultivation might improve the (biological) soil properties and increase rice yield. The aim of this study was to evaluate the effect of two different rice cultivation methods namely conventional rice cultivation method and System of Rice Intensification (SRI) rice cultivation method and two kinds organic fertilizer on improvement of soil biological properties and rice yield. In this study, a split plot experimental design was applied where rice cultivation method (conventional and SRI) was the main plot and two kinds of organic fertilizer (market waste and rice straw) was the sub plot. The treatments had four replicates. The results showed that SRI cultivation with market waste organic fertilizer could increase soil biological properties (population of microbe, fungi and soil respiration). The same treatment also increased rice growth and production. Combination of SRI and market waste organic fertilizer yielded the highest rice production (7.21 t/ha).